Samoan children's sense of place: Experiential landscapes in an urban village. (10th February 2020) - Ergler, Christina R.; Freeman, Claire; Latai, Anita
Abstract : Pacific Island communities are experiencing significant societal changes as a result of rural urban, inter‐island migration and migration to New Zealand. These relocations have significant implications for children's relationship to place. However, virtually nothing is known about children's sense of place in Samoa or places and activities that are important to them. This exploratory study worked with eight children aged 5–12 years growing up in an urban village in Samoa drawing on 'Talanoa' as research methodology and method by employing photo‐elicitation. The study provides a first snapshot of Samoan children's sense of place growing up in an urban village.